Patterns of Cell Activity in the Subthalamic Region Associated with the Neuroprotective Action of Near-Infrared Light Treatment in MPTP-Treated Mice. (14th May 2012) - Shaw, Victoria E.; Peoples, Cassandra; Spana, Sharon; Ashkan, Keyoumars; Benabid, Alim-Louis; Stone, Jonathan; Baker, Gary E.; Mitrofanis, John
Abstract : We have shown previously that near-infrared light (NIr) treatment or photobiomodulation neuroprotects dopaminergic cells in substantia nigra pars compacta (SNc) from degeneration induced by 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) in mice. The present study explores whether NIr treatment changes the patterns of Fos expression in the subthalamic region, namely, the subthalamic nucleus (STN) and zona incerta (ZI); both cell groups have abnormally overactive cells in parkinsonian cases. BALB/c mice were treated with MPTP (100–250 mg/kg) or saline either over 30 hours followed by either a two-hour or six-day survival period (acute model) or over five weeks followed by a three-week survival period (chronic model). NIr and MPTP were applied simultaneously. Brains were processed for Fos immunochemistry, and cell number was estimated using stereology. Our major finding was that NIr treatment reduced (30–45%) the increase in Fos + cell number evident in the STN and ZI after MPTP insult. This reduction was concurrent with the neuroprotection of dopaminergic SNc cells shown previously and was evident in both MPTP models (except for the 2 hours survival period which showed no changes in cell number). In summary, our results indicated that NIr had long lasting effects on the activity of cells located deep in the brain and had repaired partially the abnormal activity generated by the parkinsonian toxin.